Migration and adjustment to shocks in transition economies - Jan Fidrmuc (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
Does migration serve as an effective channel of regional adjustment to idiosyncratic shocks in transition economies? If so, one should find a strong relationship between regional unemployment and average wages on the one hand, and migration flows on the other. Yet, the evidence from transition economies indicates that the efficacy of migration in reducing inter-regional unemployment and wage differentials has been low. High wages appear to stimulate overall mobility rather than encourage a net immigration, and the effect of unemployment is statistically weak and not robust. In addition, the effect of unemployment and wages on net migration flows is economically insignificant and the overall level of migration has fallen during transition.
Keywords: F22; J61; P23; 330; Migration; Unemployment; Regional Shocks; Regionale Arbeitsmobilität; Regionaler Arbeitsmarkt; Schock; Regionale Arbeitslosigkeit; Regionale Lohnstruktur